Clinical implications of the arterial supplies and their anastomotic territories in the nasolabial region for avoiding arterial complications during soft tissue filler injection. Issue 4 (6th July 2020) - Jitaree, Benrita; Phumyoo, Thirawass; Uruwan, Sukanya; Jiirasutat, Nuttapatch; Pratoomthai, Benjamart; Tansatit, Tanvaa
Abstract: Introduction: The nasolabial fold (NLF) causes particular concern during aging in the middle face region. However, arterial complications of filler injections at this site have been continually reported during recent years. The aim of this study was to investigate the arterial locations and their anastomotic pathways related to filler injection sites in the NLF. Materials and methods: Thirty hemi‐faces of 15 embalmed Thai cadavers were dissected. Three anatomical landmarks of NLFs were assigned: the inferior margin level (NLF1), the mid‐philtral horizontal line level (NLF2), and the inferior alar level (NLF3). Ten hemi‐faces of five soft embalmed Thai cadavers underwent a modified Sihler's staining procedure to investigate the arterial anastomoses. Results: The artery closest to all of the landmarks was the facial artery. It was located inferomedial to NLF1 in 28%, and the mean distances along the X‐ and Y‐axes were 3.53 ± 2.11 mm and 3.53 ± 1.75 mm, respectively. It was also located medial to NLF2 in 52.1% with an X‐axis distance of 4.93 ± 1.53 mm. Several arteries were located close to NLF3, including the facial (33.3%), lateral nasal (33.3%), and infraorbital (30.0%) arteries. Anastomoses of the nasolabial arteries served to connect both the external–external and internal–external carotid systems. Conclusions: Several arteries are located close to NLF1–NLF3. To prevent arterial injury, the locations and anastomotic pathways, as possible sources of severe complications, should be recognized prior to NLF filler injection.